Kondom Dipasang, IMS Berkurang: Gambaran Penggunaan Kondom pada Wanita Pekerja Seks Resosialisasi Argorejo - Choiri Choiri; Kiki Olgavianita; Guruh Prayoga; Rima Meilani (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2022)
Background: The purpose of this study is to reveal the description of condom use behavior related to the incidence of STIs (Sexually Transmitted Infections) among FSW who are in Argorejo Resocialization (Sunan Kuning). Method: This research is a qualitative descriptive research. The type of data analyzed in this study was secondary data, the secondary data was obtained from the Griya ASA Clinic documents contained in the 2012 patient routine visit book. The analysis was carried out on 32 FSW who were in the Argorejo resocialization who were recorded as having routine screening at the Griya Clinic ASA. The independent variable is the use of condoms in the last week for FSW and the dependent variable is the diagnosis of FSW. Data analysis was performed using Univariate analysis. Results: The data above shows that FSW who admit to always using condoms are more likely to get STIs than those who only occasionally. From that arises the assumption that there may be a lack of knowledge about how to use condoms. Based on the data obtained from 32 respondents there was no significant difference because the sample was too small, the sample used was only people who routinely checked themselves at Griya ASA Clinic and only 32 respondents, so it could not represent the FSW population in Argorejo Resocialization Sunan Kuning has a population of 719, so the sample used is not representative and the results are not valid.